Short-term effects of reduced-impact logging on Copaifera spp. (Fabaceae) regeneration in Eastern Amazon - Klauberg C. (2017)
© 2017 by the authors.Timber management directly influences the population dynamics of tree species, like Copaifera spp. (copaíba), which provide oil-resin with ecological and economic importance. The aim of this study was to evaluate the structure and population dynamics of Copaifera in unmanaged and managed stands by reduced-impact logging (RIL) in eastern Amazon in Pará state, Brazil. Based on a stem map of the study area, 40 Copaifera trees were randomly selected, where an equal number of trees were selected in managed and unmanaged stands. A transect of 10 × 100 m was centered at each tree (50 m each side) to assess Copaifera regeneration. Transects were subdivided into ten plots, of which six were systematically chosen to assess the height, diameter and number of Copaifera seedlings and saplings. The field assessment occurred in 2011 and 2013. To estimate the amount of sunlight transmitted to the forest floor, we computed canopy cover from airborne LiDAR data. According to the results, the abundance of Copaifera seedlings/saplings was higher in managed than unmanaged stands. About 5% of Copaifera regeneration was found between 45-50 m from the Copaifera tree while ~73% of regeneration was concentrated within a 10 m radius of the Copaifera tree. We verified that the diameter distribution of Copaifera regeneration was not a negative exponential distribution, as is typical of most tree species in natural forest. Rather, the Copaifera regeneration had a spatially aggregated distribution. In this short-term analysis, the impact of timber management is not negatively affecting the population structure or dynamics of Copaifera regeneration.